SISTEM INFORMASI PENYUSUNAN LAPORAN ARUS KAS DENGAN METODE LANGSUNG UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN BERBASIS MULTIUSER (STUDI KASUS DI KANTOR NOTARIS-PPAT DINA ISMAWATI,SH.MM) - Ratna Marta Primadani (STEKOM PRESS, 2019)
The system is a framework of procedures that have one or more goals to carry out an activity or main function of the company. Computer-based information systems have now become a primary thing for information needs. Many fields have utilized computer-based information systems as a means to facilitate work. Make an accounting information system design for preparing cash flow statements so that the recording and calculation process in the company becomes computerized properly so that no errors occur. The resulting output consists of the process of cash receipts and disbursements to the preparation of financial statements. In this research, a Multiuser Based Financial Statement Information System was developed with a case study on Kator Notary-PPAT Dina Ismawati, SH.MM, where in developing this system the system development tools used are Data Flow Diagrams (DFD), Contex Diagrams, Entity Relationship Diagram (ERD) and Flowchart and using the Microsoft Viisual Basic 6.0 programming language and Ms.Sql server as the database.